First report of grapevine red globe virus (GRGV) and grapevine rupestris vein feathering virus (GRVFV) infecting grapevine (Vitis vinifera L.) in Portugal - Candresse, Thierry; Faure, Chantal; Marais, Armelle (Plant disease, 2023)
Grapevine Red globe virus (GRGV) and grapevine rupestris vein feathering virus (GRVFV) are relatively recently described grape viruses that respectively belong to the genera Maculavirus and Marafivirus in the family Tymoviridae [1]. Owing to their rather recent description, still limited information on their biology, on their molecular variability and on their geographic distribution is available. Both viruses are apparently completely or largely asymptomatic in European grapevine and have likely been overlooked in a wide range of situations (Martelli, 2014). According to sequences in GenBank, GRGV has been identified in Asia (Iran, Japan, China), the Americas (USA, Brazil) and Europe (Spain, France, Slovenia, Hungary, Czech Republic and Germany). GRVFV has been reported from the same countries but also in Oceania (New Zealand, Australia) and from a range of other countries including India, Pakistan and South Korea for Asia, Canada for North America and Switzerland, Slovakia, Italy and Russia for Europe. Evidence for the presence of GRGV and GRVFV in grapevine plants from northern Portugal (variety(ies) unknown) was obtained through the bioinformatic analysis [2] of RNASeq Illumina data obtained from phloem scrapings from five grapevine samples collected in different plots in 2016 [3]. Following grapevine genome substraction, contigs assembly and Blast-based contigs annotation using CLC Genomics Workbench, two plants, #4 and #5b, yielded contigs representing near complete GRGV genomes. The plant #4 contig integrated 474 reads (0.15% of reads for an average coverage of 10.1x) while the corresponding values for the contig for plant #5b are 2185 reads (2.4% of total reads) for a coverage of 47.2x. The two GRGV contigs show 91.4% nucleotide (nt) identity and the closest GRGV full genome sequence in GenBank, MZ451067 from Canada, shares respectively 98.9% and 91.6% nt identity with them. The near complete genome contigs have been deposited in GenBank (ON603917 and ON603918). Simultaneously, two near full length genomic contigs for GRVFV were identified from plant #5b and have also been deposited in GenBank (ON603919 and ON603920). These contigs show 84.4% nt identity to each other and were respectively assembled from 4643 (5.2% of total reads) and 5326 reads (6.0% of total reads) for respective average coverages of 102.3x and 117.3x. The closest full GRVFV genome in GenBank is MZ027155 from the USA, with 84.3-85.3% nt identity. Confirmation of the presence of GRVG and GRVFV in the doubly infected plant #5b was achieved by specific RT-PCR assays. A published assay [4] was used for GRGV and primers GRVFV-Cp-F 5'AAYCCTGTCACHCTCCACTG3' and GRVFV-Cp-R 5'TTCATGGTGGTGCCDGTGAG3' (Tm 55°C) were used for GRVFV. The obtained 447nt GRGV amplicon showed a single difference with the HTS contig while the 218 nt GRVFV amplicon showed 3 mutations as compared to one of the HTS contigs. The different grapevines had initially been sampled because they showed relatively poor and stunted growth but besides GRVFV and/or GRGV the HTS analysis indicated that they were also infected by hop stunt viroid, grapevine yellow speckle viroid 1, grapevine rupestris stem pitting virus, plus respectively a novel nepovirus (plant #4) and grapevine leafroll-associated virus 2 and grapevine Pinot gris virus (plant #5b) so that the results reported here do not shed novel light on the potential pathogenicity of GRGV or GRVFV. To the best of our knowledge, this is the first report of GRGV and GRVFV in Portugal.